Are Malaysia's Graduates Prepared The Fourth Industrial Revolution Workforce?: A systematic Literature Review - Yunos, Syuhada; Madar, Ahmad Rizal (Online Journal for TVET Practitioners, 2025)
The Fourth Industrial Revolution is defined by artificial technologies and the Internet of Things, leading to the disappearance of some jobs while creating new ones. Most emerging technologies require advanced technical expertise and academic qualifications, significantly impacting employment, education, and TVET training for skilled workers. Skilled labor is essential for economic advancement and achieving a high-income economy, making it crucial to enhance the quality and participation in TVET. This literature review identifies the new skills needed in the workforce for the Fourth Industrial Revolution, focusing on "fourth industrial revolution skills" and "graduate readiness." The literature is categorized into nine Malaysia Future-Proof Skills: 1) Creativity & Innovation, 2) Holistic, Entrepreneurial & Balance, 3) Resilience, 4) Leadership, 5) Compassion & Mindfulness, 6) Value & Ethics, 7) Flexibility & Adaptability, 8) Critical Thinking & Problem Solving, and 9) Communication & Language Proficiency. Utilizing a systematic literature review methodology and the PRISMA procedure, this study synthesizes findings from journals and industry reports. The findings suggest that the nine Future-Proof Skills are consistent with the requirements of businesses that are in search of 4IR professionals. Therefore, further research on human resource perspectives regarding 4IR skills is necessary. Strengthening these skills among Malaysian graduates is vital to fostering high-quality, future-proof talent. To thrive in the machine-human technology era of 4IR, Malaysian graduates must embrace all nine future-proof skills. This study aims to enhance understanding of 4IR skills among graduates, institutions, and industries.